Synthesis and Characterization of Hydroxyapatite (HAp) from Cerithidea Quoyii Seashell by Chemical Method - Muhamad Ariffin Zahari,; Muhammad Azib Adam,; Nur Syuhada Amira Zulkarnain,; Rosley, Rozainita (Multidisciplinary Applied Research and Innovation, 2026)
Seashells, which serve as protective and supporting exoskeletons for molluks, are typically made up of organic materials like proteins and chitin and over 95% calcium carbonate (CaCO₃). This study aims extract Calcium Oxide with the synthesis of Hydroxyapatite from Cerithidea quoyii seashell which is widely used in biomedical applications. The seashells were initially calcined at temperature 900 °C to convert calcium carbonate (CaCO₃) into calcium oxide (CaO). The calcined powder was then mixed with distilled water and phosphoric acid ranging from 0.3 M to 0.9 M before undergoing a 24-hour aging process. The resulting precipitates were centrifuged and recalcined at 800 °C. Characterization of the synthesized HAp was conducted using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM/EDX). The XRD analysis confirmed the formation of HAp through the successful conversion of CaCO₃ to CaO. XRD analysis confirmed the formation oh HAp through the successful conversion of CaCO₃ to CaO. FTIR spectra indicated the presence of phosphate (PO₄³⁻), carbonate (CO₃²⁻), and hydroxyl (OH⁻) groups, further confirming the synthesis of HAp. SEM/ EDX analysis shows the best pH concentration in obtaining the smallest ratio of Ca/P is 7.0 M. EDX analysis shows the best ratio of Ca/P atomic percentage in HAp at 9.0 M concentration phosphoric acid with 5.06.